Racial disparities in caesarean delivery among nulliparous women that delivered at term: cross-sectional decomposition analysis of Nebraska birth records from 2005-2014 - Corrine Hanson; Kaeli Samson; Ann L. Anderson-Berry; Rebecca A. Slotkowski; Dejun Su (BMC, 2022)
Abstract Background Previous studies suggest higher rates of caesarean section among women who identify as racial/ethnic minorities. The objective of this study was to understand factors contributing to differences in caesarean rates across racial and ethnic groups. Methods Data was collected from 2005 to 2014 Nebraska birth records on nulliparous, singleton births occurring on or after 37 weeks gestation (n = 87,908). Risk ratios (RR) and 95% confidence intervals (CI) for caesarean were calculated for different racial and ethnic categories, adjusting for maternal age, marital status, county of residence, education, insurance status, pre-pregnancy BMI, and smoking status. Fairlie decomposition technique was utilized to quantify the contribution of individual variables to the observed differences in caesarean. Results In the adjusted analysis, relative to non-Hispanic (NH) White race, both Asian-NH (RR 1.21, 95% CI 1.14, 1.28) and Black-NH races (RR 1.13, 95% CI 1.08, 1.19) were associated with a significantly higher risk for caesarean. The decomposition analysis showed that among the variables assessed, maternal age, education, and pre-pregnancy BMI contributed the most to the observed differences in caesarean rates across racial/ethnic groups. Conclusion This analysis quantified the effect of social and demographic factors on racial differences in caesarean delivery, which may guide public health interventions aimed towards reducing racial disparities in caesarean rates. Interventions targeted towards modifying maternal characteristics, such as reducing pre-pregnancy BMI or increasing maternal education, may narrow the gap in caesarean rates across racial and ethnic groups. Future studies should determine the contribution of physician characteristics, hospital characteristics, and structural determinants of health towards racial disparities in caesarean rates.